Eucharistic Creation: Symbol, Meaning, Infinity - Hale, Mattison (Lumen et Vita, 2017)
Christian theology finds in the Eucharist its most ancient and primary intercessory link to the presence of Christ. It is here, the Faith teaches, that the risen Lord can be ritually and truly encountered. The precise nature of the encounter, however, has been explored and explained variously over the past two millennia. Louis-Marie Chauvet in Symbol and Sacrament has proposed a postmodern account of being rooted in Eucharistic symbolic exchange. However, Chauvet's position inherits certain weaknesses from his sources, Heidegger and Derrida. Certain of these can be amended by approaching the question from the perspective of theological aesthetics. This paper attempts to raise possible aesthetic contributions to Eucharistic theology in light of Chauvet by drawing on David Bentley Hart’s work, The Beauty of the Infinite: The Aesthetics of Christian Truth. While Chauvet rightly highlights the symbolic mediacy of human access to being, Hart's aesthetic theology can be used to supplement Chauvet's account particularly in its explanation of gift and desire. Beginning with the analogia entis, Hart proceeds to explain creation in terms of analogia delectationis and finally analogia verbi. This provides a basis for understanding all of being Eucharistically; the mirror of being is the Sacrament itself. Thus “creation” describes not only a former event at the beginning of time, but a particular relation to the Creator.